2021
DOI: 10.1016/j.nicl.2020.102535
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reserve hypothesis in frontotemporal dementia: A FDG-PET study

Abstract: Highlights The cognitive reserve hypothesis is also applicable for FTD. The educational level predicts left-temporal hypometabolism in FTD. Residualized cognitive performance is positively correlated with education. Residualized cognitive performance is negatively correlated with hypometabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…This concept has been investigated in greater detail in FTD, but similar themes are also emerging in ALS. The level of cognitive reserve appears to predict cognitive performance and the degree of brain imaging abnormalities (290)(291)(292). These observations suggest that patient-specific factors influence the chronology of clinically evident symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This concept has been investigated in greater detail in FTD, but similar themes are also emerging in ALS. The level of cognitive reserve appears to predict cognitive performance and the degree of brain imaging abnormalities (290)(291)(292). These observations suggest that patient-specific factors influence the chronology of clinically evident symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The process of knowledge acquisition is also a process of brain development, and a good education means a better cognitive reserve (Borroni et al 2009;Rodriguez et al 2019;Rouillard et al 2017). A recent study explored the association between education level and [ 18 F]-fluorodeoxyglucose positron-emission-tomography (FDG-PET) hypometabolism (Beyer et al 2021). This corroborated the association between high education level and relatively high cognitive performance.…”
Section: Discussionmentioning
confidence: 87%
“…Using this concept, people whose cognitive performance is superior to the predicted by the pathology have a high reserve, whereas people who perform poorer than predicted have a low reserve [85]. This framework has been helpful as an index in several studies [33,35,49,86]. However, one weakness of this method is that the residual may result from a mixture of random prediction error, and then a portion of the variable could be attributed to reserve.…”
Section: Discussionmentioning
confidence: 99%
“…Sharp and Gatz have suggested that "education is best described as a proxy for a trajectory of life events… that either increase or decrease an individual's risk for dementia" [36]. Furthermore, as Beyer et al point out, years of education is not the only proxy that has been recognised to assess cognitive reserve [49]; other factors such as occupation and life activities have been recognised as contributors to the overall reserve of a person [43,87]. Livingston et al in the Lancet Commission on dementia also explained that cognitive reserve is changeable, and it uses proxy measures such as residual approach, education, the complexity of occupation, and life activities [88][89][90].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation